Endodontic and Surgical Management of External Cervical Root Resorption: A Case Report - Fatemeh Bonyadimanesh; Mohammadreza Abrishami (Clinical Case Reports, 2026)
ABSTRACT This study describes the treatment of tooth #9 exhibiting external cervical root resorption (ECR) and apical root resorption. A therapeutic approach—including root canal therapy with MTA apexification, surgical debridement of resorptive tissue at the ECR site, and sealing of the defect—was necessary to eliminate the infection.